2008
DOI: 10.1590/s1415-47572008000300027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mitochondrial gene rearrangements and stability of the origin of light strand replication

Abstract: Mitochondrial gene rearrangements are much more frequent in vertebrates than initially thought. It has been suggested that the origin of light strand replication could have an important role in the process of gene rearrangements, but this hypothesis has never been tested before. We used amphibians to test the correlation between light-strand replication origin thermodynamic stability and the occurrence of gene rearrangements. The two variables were correlated in a non-phylogenetic approach, but when tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Our results supported the observation that the hotspot of gene rearrangement was adjacent to the origin of light-strand replication (San Mauro et al, 2006). The widespread occurrence of gene rearrangement among different vertebrate groups has been examined in relation to variability in the thermodynamic stability of the light-strand replication origin (Fonseca & Harris, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Our results supported the observation that the hotspot of gene rearrangement was adjacent to the origin of light-strand replication (San Mauro et al, 2006). The widespread occurrence of gene rearrangement among different vertebrate groups has been examined in relation to variability in the thermodynamic stability of the light-strand replication origin (Fonseca & Harris, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The sequence 5'-ACCGG-3' but conserved motif 5'-GCCGG-3' is exactly shown at the base of the stem within the tRNA Cys gene. Motif 5'-GCCGG-3' is often found in many vertebrates (Zardoya et al, 1995;Macey et al, 1997;Oh et al, 2007b;Fonseca and Harris, 2008), even in scombrid (Manchado et al, 2004; Fig. 2B-F).…”
Section: Feature Of Non-coding Regionsmentioning
confidence: 98%
“…However, in M. f. calamorum, we found the T-rich sequence was replaced by Poly C in the O L loop region .The adjacent sequence 5′-TAAGG-3′ at the base of O L stem (not the 5′-GCCGG-3′) was found in three genus Microtus species. The motif 5′-GCCGG-3′ was found in many vertebrates (Fonseca and Harris, 2008;Macey et al, 1997;Zardoya et al, 1995) and was reported to be critical for human mtDNA replication (Hixson et al, 1986). (Huang et al, 1995;Luo et al, 2000): (1) (Hong, 1981).…”
Section: Control Region and Putative Origin Of Replication For The LImentioning
confidence: 99%